(untitled) - Krugman, Paul R (Cambridge, Mass, 1990)
Paul Krugman's popular guide to the economic landscape of the 1990s has been revised and updated to take into account economic developments of the past three years. New material in the third edition includes:- A new chapter--complete with colorful examples from Lloyds of London and Sumitomo Metals--on how risky behavior can lead to disaster in private markets.- An evaluation of the Federal Reserves role in reining in economic growth to prevent inflation, and the debate over whether its growth targets are too low.
Keywords: Economic forecasting,Dự báo kinh tế; United States,Mỹ